Prácticas de autoabasto en la memoria de un pueblo en la Región Centro-Oriente de Morelos, México - Saldaña Ramírez, Adriana (2017)
In this article the decline of self-supply practices is analyzed,focus in the “milpa” production, hunting and gathering, in the community of Tenextepango, Morelos. They had a central rol in the strategies of social reproduction of farming families until the second half of the twentieth century, however with the introduction of commercial production to supply nearby Mexico City, transformations were to the detriment of the traditional practices, remaining only in the memory of several generations. This process increased the vulnerability of rural families.